Effect of urbanization on mesoscale circulation over Metro Manila and its associated rainfall - NIVAGINE, NIEVARES (Archīum Ateneo, 2010)
Metro Manila evidently is gone through transformation from urban to highly urbanized region in the country. The interaction of wind flow pattern complexity and the affect of urbanization leads to changes of mesoscale circulation and consequently the time